Endogenous approach to the principle of retaliation in base models of strategic trade policy - Rynarzewski, Tomasz (Economics and Business Review, 2003)
The aim of the paper is to examine the effects of endogenous approach to the principle of retaliation in base models of strategic trade policy in the sphere of welfare. Two main models are considered: the model of homogeneous international duopoly with behaviours according to Cournot's ( Brander - Spencer) principles of quantitative competition and the model of heterogeneous international duopoly with behaviours according to Bertrand (Eaton - Grossman) principles of price competition. The base models of strategic trade policy do not take into account the possibility of participation of the governments in a strategic game on imperfect market but they only take into account mutual behaviour of enterprises. Including the principle of retaliation in the model based on Cournot's quantitative competition leads to "the prisoner's dilemma" which means that it is impossible to reconcile domestic rationality with international rationality while making decisions as regards behaviour on the market. Such a dilemma does not occur in the case of the model based on the principles of price competition because both countries achieve welfare benefits due to the fact that one of them applies the instrument of export tax. However, it may be concluded that although under quantitative competition the mutual implementation of export subsidy can lead to unfavourable consequences for the level of welfare in both countries, it is still possible to solve "the prisoner's dilemma" through various forms of a long-term co-operative game. On the other hand, under price competition where there is no contradiction between domestic rationality and international rationality, the consequences for the world economy may be less favourable because when both countries can achieve benefits neither of them will be interested in returning to free trade. (original abstract)